2008
DOI: 10.1016/j.jnoncrysol.2007.10.062
|View full text |Cite
|
Sign up to set email alerts
|

On the development of single and multijunction solar cells with hot-wire CVD deposited active layers

Abstract: We present an overview of the scientific challenges and achievements during the development of thin film silicon based single and multijunction solar cells with hot-wire chemical vapor deposition (HWCVD) of the active silicon layers. The highlights discussed include the development of Ag/ZnO coatings with a proper roughness and morphology for optimal light trapping in single and multijunction thin film silicon solar cells, studies of the structural defects created by a rough substrate surface and their influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…It was found by several groups that a lower filament temperature is beneficial for the material quality [8,9]. However, under the conditions used in this study, high quality a-Si:H [4,5] and µc-Si:H [6] material are obtained at high deposition rates (1 nm/s and 0.2 nm/s respectively).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 79%
See 1 more Smart Citation
“…It was found by several groups that a lower filament temperature is beneficial for the material quality [8,9]. However, under the conditions used in this study, high quality a-Si:H [4,5] and µc-Si:H [6] material are obtained at high deposition rates (1 nm/s and 0.2 nm/s respectively).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 79%
“…15 cm length, in electrical series connection, they were first annealed in vacuum (background pressure b10 − 7 mbar) for 3 h at a constant current of 12.5 A (2050°C) to remove impurities. Depositions were performed at a constant current of 10.5 A (~1750°C) with a partial silane pressure of either 2 Pa during typically 10 min (a-Si:H [4,5]) or 0.25 Pa for almost 3 h (µc-Si:H [6]). Prior to every subsequent exposure to silane, the filaments were annealed for 30 min at a constant current of 12.5 A (1950-2050°C).…”
Section: Methodsmentioning
confidence: 99%
“…The results indicate that the optical absorption of the a-Si:H layer increases with increasing aspect ratios due to their broadband absorption. Nevertheless, the electrical properties are restricted by steep surface roughness [15]. Enhanced photovoltaic characteristics are demonstrated for the nanostructured glass superstrate with a moderate aspect ratio of 0.16.…”
Section: Introductionmentioning
confidence: 99%
“…12 Considerable attention is currently given to the correlation of the light-trapping effects with the morphology of the TCOSi interface. [12][13][14][15][16] In particular, it has been realized that the size of the features in the texture is important for the scattering mechanism at the interface and thus for the resulting light-trapping efficiency. 15 The typical features of the presently used textures have lateral sizes between several lm and $700 nm.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that silicon thin films grown over very rough surfaces become defective. 16 Another important limitation of this absorption enhancement approach is that the performance of the back reflectors, used to additionally improve the absorption, deteriorates with increasing roughness. 16 Therefore, the optimization of solar cells grown on textured substrates with respect to a geometrical absorption enhancement is a matter of compromise.…”
Section: Introductionmentioning
confidence: 99%